The political economy of oil and human development in Africa - Leicher, Keri (My University, 2012)
This thesis looks at the relationship between oil wealth and human development in Africa. Given that so many hydrocarbon rich countries across the continent have failed to harness such revenues to achieve meaningful development, this paper constructs statistical models to determine the exact workings of the paradox of plenty. In doing so, it identifies corruption and, more importantly, political structure and regime type as the primary hindrances to unlocking natural and economic benefits of oil production. This paper therefore illustrates that the resource curse in Africa is a by-product of poor governance only. The case studies of Equatorial Guinea and Gabon further highlight this reality.
M.A. University of the Witwatersrand, Faculty of Humanities, 2012